Role of Psychological factors on Chinese Players Performance with the Mediating Role of Recognition - Zhang, JianHua; YingJie Zhang; Lei Zhang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Objective: Performances by players especially from China are not as good as they can be. There are various factors involved due to which the players' performance is not as it is required. Besides various other factors, psychological factors are the major reason due to which the players are unable to perform well. Hence the primary objective of this study is to investigate the role of psychological factors on Chinese players' performance. Method: Quantitative research method was adopted to conduct the survey aim to collect primary data from the 620 respondents of this study. Partial Least Square (PLS) was used to analyze the primary data aim to achieve the end results of this study. Conclusion: According to the results of this study, psychological factors such as environment, motivation, Ambition, and social status have a direct relationship with players' performance. Moreover, recognition besides directly affected by the aforementioned psychological factors also has a direct relationship with player performance. Recognition also mediates between the relationship of the aforementioned psychological factors and players' performance. Practical Implication: This study provides sufficient knowledge and boosts to the players to enhance and maintain their performances.